Shahnama studies II
1 online resource (xx, 316 pages, [26] pages of plates)
Keywords: This volume explores different aspects of the reception of Firdausi’s Shahnama or ‘Book of Kings’, both within Iran and in neighbouring lands. Later poets and writers not only looked to Firdausi’s work for a model, but supplemented its stories with other narratives or absorbed the characters and the moral values of the poem into their own works. Several chapters focus on the literary traditions fed by the Shahnama , including reports of the continuing oral performances of its more popular stories. Others discuss Firdausi’s impact on the creative imagination of the miniature painters who illustrated manuscript copies of the Shahnama in the courts of the Ottoman Empire, Moghul India, and the Central Asia Khanates up till the seventeenth century. Contributors include Gabrielle van den Berg, Francesca Leoni, Farhad Mehran, Bilha Moor, Adeela Qureshi, Ravshan Rahmoni, Julia Rubanovich, Karin Ruehrdanz, Jan Schmidt, Ivan Steblin-Kamenski, Zeren Tanindi, Lâle Uluç, Evangelos Venetis, Olga Yastrebova, and Marjolijn van Zutphen.